2021
DOI: 10.1111/jog.14639
|View full text |Cite
|
Sign up to set email alerts
|

CircRNA DNA methyltransferase 1 silence inhibits breast cancer development by regulating micoRNA‐485‐3p/zinc finger E‐box binding homeobox 1 axis

Abstract: Background Circular RNAs (circRNAs) are associated with tumorigenesis of breast cancer. Nevertheless, how and whether circRNA DNA methyltransferase 1 (circ‐DNMT1) controls breast cancer development remains poorly understood. Methods The paired tumor and paracancer tissues (n = 41) were obtained from breast cancer patients. Circ‐DNMT1, microRNA (miR)‐485‐3p, and zinc finger E‐box binding homeobox 1 (ZEB1) abundances were measured by quantitative reverse transcription polymerase chain reaction and western blot. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…circDNMT1 was overexpressed in breast cancer tissues. As an miRNA sponge, circDNMT1 maintains the highly proliferative state of breast cancer by regulating the miR-485-3p/ZEB1 axis ( 20 ). Another study showed that circDNMT1 promotes nuclear translocation of p53 and AUF1 and activates autophagy to increase survival capabilities of breast cancer ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…circDNMT1 was overexpressed in breast cancer tissues. As an miRNA sponge, circDNMT1 maintains the highly proliferative state of breast cancer by regulating the miR-485-3p/ZEB1 axis ( 20 ). Another study showed that circDNMT1 promotes nuclear translocation of p53 and AUF1 and activates autophagy to increase survival capabilities of breast cancer ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…Hsa_circ_0049224 (circDNMT1) is a newly identified circRNA in cancer treatment. It has been reported to be an autophagy modifier and miRNA sponge that potentiates breast cancer development ( 19 , 20 ). Since the biological functions of circDNMT1 in GC remain unknown, in this study, we aimed to explore the role and underlying mechanisms of circDNMT1 in GC.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to miR-1246, fewer investigations have addressed the role of miR-485-3p in cancer, but, with few exceptions [ 65 , 66 , 67 ], it appears to function as a tumor-suppressor miRNA. Its expression in tumor tissue was found to be downregulated in prostate cancer [ 68 , 69 ], glioblastoma [ 70 ], breast and colorectal cancer [ 71 , 72 , 73 , 74 ], osteosarcoma [ 75 ] and renal carcinoma [ 76 ]. Interestingly, in some of those studies, the reduced expression of miR-485-3p was linked to upregulation of a long non-coding RNA (LncRNA) [ 75 ] or a circular RNA [ 72 , 74 , 76 ] able to sponge the miRNA, thus leading to enhanced expression of target genes promoting tumor cell proliferation, survival and invasiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Its expression in tumor tissue was found to be downregulated in prostate cancer [ 68 , 69 ], glioblastoma [ 70 ], breast and colorectal cancer [ 71 , 72 , 73 , 74 ], osteosarcoma [ 75 ] and renal carcinoma [ 76 ]. Interestingly, in some of those studies, the reduced expression of miR-485-3p was linked to upregulation of a long non-coding RNA (LncRNA) [ 75 ] or a circular RNA [ 72 , 74 , 76 ] able to sponge the miRNA, thus leading to enhanced expression of target genes promoting tumor cell proliferation, survival and invasiveness. In the circulation, lower levels of miR-485-3p were detected in serum and serum exosome of glioblastoma patients as compared with healthy subjects [ 77 , 78 ].…”
Section: Discussionmentioning
confidence: 99%
“…Circ-DNMT1 interfered with miR-485-3p-induced targeting of ZEB1. There was an evident reduction in the tumor growth in mice inoculated with circ-DNMT1-silenced-MDA-MB-231 cancer cells (61).…”
Section: Circular Rnas Dnmt1mentioning
confidence: 96%